2020
DOI: 10.3390/antiox9090793
|View full text |Cite
|
Sign up to set email alerts
|

Properdin Modulates Complement Component Production in Stressed Human Primary Retinal Pigment Epithelium Cells

Abstract: The retinal pigment epithelium (RPE) maintains visual function and preserves structural integrity of the retina. Chronic dysfunction of the RPE is associated with retinal degeneration, including age-related macular degeneration (AMD). The AMD pathogenesis includes both increased oxidative stress and complement dysregulation. Physiological sources of oxidative stress in the retina are well known, while complement sources and regulation are still under debate. Using human primary RPE (hpRPE) cells, we have estab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 87 publications
1
23
0
Order By: Relevance
“…Complement components are locally expressed by different retinal cell types and by ARPE-19 cells (27,30,31,39). Here, we showed that the complement regulator FHR3 enhanced complement expression and secretion of RPE cells (Fig.…”
Section: Fhr-3 Increased Endogenous Complement Activationmentioning
confidence: 64%
See 4 more Smart Citations
“…Complement components are locally expressed by different retinal cell types and by ARPE-19 cells (27,30,31,39). Here, we showed that the complement regulator FHR3 enhanced complement expression and secretion of RPE cells (Fig.…”
Section: Fhr-3 Increased Endogenous Complement Activationmentioning
confidence: 64%
“…We showed that FHR-3 is an in ammatory stimulator and may serve as a damage-associated sensing molecule for RPE cells (59). Just recently, we identi ed RPE cells as one of the major sources of complement expression in the mouse retina (39), hpRPE cells (27,31) and in ARPE-19 cells (30). Here, we reported that FHR3 induced complement activation in cultured RPE cells.…”
Section: Fhr-3 a Danger Associated Molecule Within The Eye?mentioning
confidence: 70%
See 3 more Smart Citations